Developing a research and action agenda for examining urbanization and caregiving: examples from southern and eastern Africa - Engle, Patrice L.; Menon, Purnima; Garrett, James L.; Slack, Alison T. (International Food Policy Research Institute, 1997)
The UNICEF-expanded model for nutrition is used to analyze the circumstances of care in urban environments. The model postulates that there are six major types of care behaviors: feeding and breast-feeding, food preparation and handling, hygiene behavior, psychosocial care, care for women, and home health practices. These behaviors require the resources of education and knowledge of the caregivers, the physical and mental health of caregivers, autonomy in decisionmaking, time availability, and the social support of the family and community in order to ensure adequate care for the child. This paper describes each of these constraints, and two of the behaviors (feeding and health care utilization) in urban and rural areas. Data from Demographic and Health Surveys (DHS) in eight countries in Eastern and Southern Africa were used to illustrate how existing data can be used to examine care, and what research questions remain to be addressed to understand care in the urban setting. A number of differences favor the urban environment over the rural environment: in general, child malnutrition is less (though this may not be true in poor urban areas), maternal education levels are higher, and knowledge of health care practices is greater. On the other hand, breast-feeding seems to be less frequent and of shorter duration. It is argued that care may be even more important in urban rather than rural settings for child health and survival in low-income neighborhoods. Caution is needed when comparing urban and rural areas, however, because there are often enormous care, health, and nutrition differences between poor-income and middle-to-high-income areas of cities. Through the application of the expanded UNICEF model, a research agenda was developed.